2015
DOI: 10.15394/ijaaa.2015.1045
|View full text |Cite
|
Sign up to set email alerts
|

Aviation Bird Hazard in NEXRAD Dual Polarization Weather Radar Confirmed by Visual Observations

Abstract: Acknowledgements. This research benefited from the government-sponsored NSF Unidata program and software, specifically the IDV software package provided by Unidata (www.unidata.ucar.edu/software/). We thank three anonymous reviewers who made suggestions that strongly improved the manuscript, and David Ison and Chip Wolfe of IJAAA who assisted with the inclusion of the animation in the metadata for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We suggest that data on validated scatterer identity, density, and body orientation with respect to the radar; spatial patterns of echo return; and natural history will advance approaches to bioscatter classification. The resulting future algorithms will enable the application of data from weather surveillance radar to assist in improving flight safety [67,84], monitoring the movements of agricultural pest and disease vectors [85], making informed conservation decisions [86,87], and providing the public with information that will enhance wildlife viewing opportunities [88].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that data on validated scatterer identity, density, and body orientation with respect to the radar; spatial patterns of echo return; and natural history will advance approaches to bioscatter classification. The resulting future algorithms will enable the application of data from weather surveillance radar to assist in improving flight safety [67,84], monitoring the movements of agricultural pest and disease vectors [85], making informed conservation decisions [86,87], and providing the public with information that will enhance wildlife viewing opportunities [88].…”
Section: Discussionmentioning
confidence: 99%
“…Once dual-polarization was available, some investigators used one or more of the approaches mentioned above to identify the type of scatterer and to characterize the values of the polarimetric variables produced by that type of scatterer [36]. In most of the studies that have reported values of polarimetric variables from biological scatterers, the authors made assumptions about the identity of the type of scatterer before the analysis of the polarimetric data, but in a few cases the investigators knew the identity of the scatterer [66] or they knew about the departures of purple martins and other swallows from nighttime roosts [18,51,67,68] and the exodus of free-tailed bats from their daytime roosts [18,49,51,69]. In our study, we recorded legacy and polarimetric data from known biological scatterers and rain and generated histograms of values (Figure 1) for each type of scatterer.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation